Barriers general education teachers face regarding the inclusion of students with autism - Al Jaffal, Mohammed (Frontiers in Psychology, 2022)
As the number of students diagnosed with autism spectrum disorder (ASD) present in general education (GE) classrooms has increased in the past few decades, GE teachers must adapt to meet the needs of these students. Laws and regulations require students with ASD to be educated in the least restrictive environment, as well as that they be instructed by the teachers who were qualified to teach them. Unfortunately, GE teachers face the challenges supporting students with ASD in GE settings. This qualitative research investigates the barriers that prevent teachers from successfully implementing an inclusive environment in the GE classroom. In total, four elementary school teachers at a school in the northeast of the United States were interviewed and observed. The data were analyzed to identify emerging themes. The findings showed that GE teachers lack training in how to work with students with ASD in their GE classrooms, lack collaboration opportunities with their special education colleagues to better support their students with ASD, and are not provided sufficient resources by their schools and programs to create an appropriate inclusive environment in their GE classrooms. Based on these findings, certain improvements in professional development offerings for in-service general educators on how to teach students with ASD are recommended, such as providing broader training programs that give teachers the opportunity to practice interventions and teaching plans for inclusive classrooms and receive feedback from the training instructor(s). Furthermore, certain additions to the curriculum of pre-service university education programs for GE teachers are suggested. In addition, the research found that schools must make certain resources, including technology, available to GE teachers to meet the requirements of United States law regarding educating students with disabilities, including ASD, in the least restrictive environment, which is the GE classroom.